Outcome Analysis of Surgical Timing in Pediatric Orbital Trapdoor Fracture with Different Entrapment Contents: A Retrospective Study - Pei-Ju Hsieh; Han-Tsung Liao (MDPI AG, 2022)
Orbital trapdoor fracture occurs more commonly in pediatric patients, and previous studies suggested early intervention for a better outcome. However, there is no consensus on the appropriate timing of emergent intervention due to the insufficient cases reported. In the current retrospective study, we compared the outcomes of patient groups with different time intervals from injury to surgical intervention and entrapment content. Twenty-three patients who underwent surgery for trapdoor fracture between January 2001 and September 2018 at Chang Gung Memorial Hospital were enrolled. There was no significant difference in diplopia and extraocular muscle (EOM) movement recovery rate in patients who underwent surgery within three days and those over three days. However, among the patients with an interval to surgery of over three days, those with muscle entrapment required a longer period of time to recover from EOM movement restriction (p = 0.03) and diplopia (p = 0.03) than those with soft tissue entrapment. Regardless of time interval to surgery, patients with muscle entrapment took longer time to recover from EOM movement restriction (p = 0.036) and diplopia (p = 0.042) and had the trend of a worse EOM recovery rate compared to patients with soft tissue entrapment. Hence, we suggested that orbital trapdoor fractures with rectus muscle entrapment should be promptly managed for faster recovery.